INDONESIA INTEREST IN INTERNATIONAL LABOR ORGANIZATION (ILO) CONVENTION NO.189 - Debora Panca Anugrah; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research aims to analyze, Indonesia Interest in ILO convention No. 189 on Decent Works for Domestic Workers. Indonesia has massive number of domestic workers caused by low quality of education. Therefore, Indonesia agreed on creation of ILO Convention No.189 in protecting their society that works as domestic workers. However, in the early of ILO Convention No.189 agreement creation in 2011, Indonesia has not ratified this Convention to 2013. If Indonesia has ratified this convention previously, then Indonesia would protected their society that works as domestic workers. Furthermore, Indonesia domestic workers bargaining power will increase and declin on Indonesia domestic workers demand. If Indonesia ratified this convention, Indonesia will sustain their unskilled social welfare (low quality of education) constantly working and gaining national income from domestic workers works overseas in foreign exchange. Qualitative method performed in analyzing this study by collecting data and fact from several literatures, such as from books, journals, mass media and website. According to realist approach, Joshep M Grieco used as supported theory in analyzing Indonesia Interest in ILO Convention No. 189 as participant in international agreement. This research is find that, Indonesia is not be able yet in complying ILO Convention No.189 provisions because of their society condition, another importance in sustaining national existences and social welfare. Keywords: convention, ratification, domestic workers, national interest.